Trend Sound Horeg Pada Pawai Budaya Masyarakat Kabupaten Pati: Studi Pergeseran Tradisi dan Konflik Sosial - Muhamad Adi Fahriza; Kamilia Hamidah (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2026)
This study examines the trend of sound horeg usage in cultural parades within the community of Pati Regency as a manifestation of shifting traditions and an emerging trigger of social conflict. Initially serving as a supporting entertainment medium in community celebrations, sound horeg has increasingly dominated cultural parades, leading to the marginalization of traditional arts and the erosion of local cultural values. This phenomenon has transformed cultural parades from spaces of cultural preservation into arenas of modern entertainment and social prestige, which in turn generates social tensions related to noise disturbance, public order, and differing perspectives on cultural authenticity. This research employs a qualitative field research method through observation, in-depth interviews, and documentation. Data were analyzed using a descriptive-analytical approach grounded in Koentjaraningrat’s cultural theory and Karl Marx’s social conflict theory. The findings indicate that while sound horeg contributes to local economic activity and youth expression, it simultaneously intensifies social conflict and accelerates the shift away from traditional cultural meanings. Therefore, balanced cultural management is required to minimize conflict without eliminating local cultural values.